Noções de saúde e doença na tradição de Orixá e o papel do sacrifício - Souza, Robson Max de Oliveira (2013)
The present work intends to approach the notion of health in religions connected to the Cult of the Orishas, based on the fundamental concepts of their religious and cultural tradition in its conception of person. Makes an ethnographic presentation of Candomblé of Ketu nation, originating from the Yoruba ethnic group, which arrived in Brazil on batches of enslaved Africans, especially from the nineteenth century and the tradition of the Orishas, originating from African priests of Yoruba, came to Brazil there are about 20 years. The elements that compose the Orishas religion, necessary to understand the vision of health and disease and the therapeutic process for healing, as the offerings and sacrifices, are placed into the body of the work as a necessary path for the approximation to this universe.